Performance Management in the Public Sector of Albania - SINAJ, Zamira; NEXHIPI, Olta; SULAJ, Mjaftesa (Theoretical and Practical Research in Economic Fields, 2024)
In the realities of today's economy, the development of good governance in the public sector is one of the most important tasks of the authorities. If actions on the part of the authorities are not conducive enough, it can cause a multitude of negative consequences for the country's economy and the living standards of its citizens, as well as for the country. Therefore, an assessment of governance by the authorities in different countries around the world is a relevant research topic. The analysis is carried out for Albania in Vlora. The research aims to show how effective public administration is in the public sector in the country now. The main methods used in the study were analysis, forecasting, abstraction, and the historical method. The study included a contemporary assessment of the state of efficiency governance in Albania. It was shown that there are problems in this area due to the socialist past of the country. In addition, difficulties with the corruption component remain relevant, which requires urgent action and finding new methods to counter it. The work also assessed the current state of the Vlora region. It was shown that despite the serious difficulties associated with the outbreak of the COVID-19 crisis, the region is developing quite strongly. The reason for this is, among others, the policy formulated by the public authorities, which aimed to support local producers and medium and small enterprises, as well as to create policies to promote domestic tourism. This paper brings new insights into the field of public sector management, as well as a better understanding of the functioning of the Albanian economy.